March of the suffragettes : Rosalie Gardiner Jones and the march for voting rights - Jack, Zachary Michael, 1973- (Zest Books, 2016)
Shares the story of how "General" Rosalie Gardner Jones marched an army of women nearly one hundred seventy-five miles to win support for voting rights for women.